Association of GTF2IRD1–GTF2I polymorphisms with neuromyelitis optica spectrum disorders in Han Chinese patients - Jing-Lu Xie (Neural Regeneration Research, 2019)
Variants at the GTF2I repeat domain containing 1 (GTF2IRD1)–GTF2I locus are associated with primary Sjögren’s syndrome, systemic lupus erythematosus, and rheumatoid arthritis. Numerous studies have indicated that this susceptibility locus is shared by multiple autoimmune diseases. However, until now there were no studies of the correlation between GTF2IRD1–GTF2I polymorphisms and neuromyelitis optica spectrum disorders (NMOSD). This case control study assessed this association by recruiting 305 participants with neuromyelitis optica spectrum disorders and 487 healthy controls at the Department of Neurology, from September 2014 to April 2017. Peripheral blood was collected, DNA extracteds and the genetic association between GTF2IRD1–GTF2I polymorphisms and neuromyelitis optica spectrum disorders in the Chinese Han population was analyzed by genotyping. We found that the T allele of rs117026326 was associated with an increased risk of neuromyelitis optica spectrum disorders (odds ratio (OR) = 1.364, 95% confidence interval (CI) 1.019–1.828; P = 0.037). This association persisted after stratification analysis for aquaporin-4 immunoglobulin G antibodies (AQP4-IgG) positivity (OR = 1.397, 95% CI 1.021–1.912; P = 0.036) and stratification according to coexisting autoimmune diseases (OR = 1.446, 95% CI 1.072–1.952; P = 0.015). Furthermore, the CC genotype of rs73366469 was frequent in AQP4-IgG-seropositive patients (OR = 3.15, 95% CI 1.183–8.393, P = 0.022). In conclusion, the T allele of rs117026326 was associated with susceptibility to neuromyelitis optica spectrum disorders, and the CC genotype of rs73366469 conferred susceptibility to AQP4-IgG-seropositivity in Han Chinese patients. The protocol was approved by the Ethics Committee of West China Hospital of Sichuan University, China (approval number: 2016-31) on March 2, 2016.